TOX expression and role in CTCL. (26th June 2016) - McGirt, L.Y.; Degesys, C.A.; Johnson, V.E.; Zic, J.A.; Zwerner, J.P.; Eischen, C.M.
Abstract: Background: Cutaneous T‐cell lymphomas (CTCL) are skin malignancies including mycosis fungoides (MF) and CD30 + lymphoproliferative disorders (LPD). In early disease, CTCL can be difficult to diagnose, especially in MF for which there is no reliable diagnostic marker. MF/CTCL have increased expression of thymocyte selection‐associated HMG box protein (TOX). Although TOX has been proposed to be a diagnostic marker for MF, further validation studies are needed. Moreover, it is unclear what drives TOX expression or its role in MF/CTCL. Objective: We hypothesize evaluation of TOX levels across a spectrum of CTCL, including MF precursor (large plaque parapsoriasis, LPP), will help elucidate the implications of altered TOX expression. Materials and Methods: TOX staining was performed in MF, CD30 + LPD, LPP as well as benign inflammatory dermatoses (BID) and normal skin (NS). CTCL cell lines were utilized to evaluate the regulation of TOX. Results: Positive TOX expression was identified in 73.6% of MF cases and in 31.6% of BID/NS. TOX had a positive predictive value (PPV) for MF of 86.7% and a negative predictive value (NPV) of 48.1%. TOX expression in MF was detected more commonly in Black patients ( P = 0.015) and less commonly in transformed MF ( P = 0.045). LPP had positive TOX staining in 70.0%. In CTCL cells, GATA3 knockdown decreased TOX mRNA and protein expression. TOX expression also decreased in the presence of CTCL therapeutics. Conclusion: Our data indicate that TOX is useful as a diagnostic marker in MF. Moreover, TOX expression was evident in LPP, indicating it may have a previously unappreciated role in the development of MF. Finally, our data suggest that GATA3 regulates TOX, revealing insight into TOX regulation.